High Sulfur Content Polymer Nanoparticles Obtained from Interfacial Polymerization of Sodium Polysulfide and 1, 2, 3‐Trichloropropane in Water. Issue 11 (7th April 2015) - Lim, Jeewoo; Jung, Unho; Joe, Won Tae; Kim, Eui Tae; Pyun, Jeffrey; Char, Kookheon; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> Sulfur‐rich materials have recently attracted keen interest for their potentials in optical, electrochemical, and pesticidal applications as well as their utility in dynamic covalent bond chemistry. Many sulfur‐rich polymers, however, are insoluble and processing methods are therefore very limited. The synthesis and characterization of water‐dispersible polymer nanoparticles (NPs) with the sulfur content exceeding 75% by weight, obtained from the interfacial polymerization between 1, 2, 3‐trichloropropane and sodium polysulfide in water is reported here. The interfacial polymerization yields well‐defined sulfur‐rich NPs in the presence of surfactants, which are capable of serving a dual role as a phase transfer catalyst on top of emulsifiers. Such dual role allows for the control of the product NP size by varying its concentration. The surfactants can be easily removed by centrifugation and redispersion in water is also reported here. The resulting sulfur‐rich NPs are characterized through elemental analysis, dynamic light scattering, ζ‐potential measurements, and scanning electron microscopy.